Dampak melihat dan menonton pornografi: Perspektif dari berbagai studi kasus literatur - Hasnah, Nur (Maliki Interdisciplinary Journal, 2024)
Using smartphones and accessing the internet without limits and filtering makes it very likely that users will be exposed to pornographic content, either accidentally or intentionally because there is no supervision or supervision. 91.25% of smartphone and internet users have been exposed to pornographic content. When accessing or opening the internet, this content appears accidentally on the social media homepage or in advertisements. There are also individuals who deliberately use smartphones and the internet to access pornographic content as much as 35%, pornographic content can be in the form of films, videos or photos or images. Pornography has a huge impact on individuals who see, read or watch it, especially those who are addicted to pornography. For example, it can make someone have difficulty focusing, have difficulty concentrating, commit crimes, damage their land, give rise to negative behavior, lose enthusiasm for activities, and their days are filled with anxiety.